1998
DOI: 10.1159/000027375
|View full text |Cite
|
Sign up to set email alerts
|

The Results of Trabeculectomy with and without Mitomycin C in Young Patients

Abstract: The results of primary trabeculectomy with and without mitomycin C (MMC) were evaluated in young glaucoma patients. The patients, 15–40 years of age, were divided into two main groups and two subgroups. In group IA, primary Cairns type trabeculectomy was performed in 24 eyes of 24 patients with juvenile glaucoma; in group IB, trabeculectomy + MMC 0.4 mg/ml in 3 min was done in 20 eyes of 20 patients with juvenile glaucoma; in group IIA, primary trabeculectomy was performed in 20 eyes of 20 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 11 publications
3
14
0
Order By: Relevance
“…However, most of those reports are based in heterogeneous groups of patients. [2][3][4][5][6][7][8][11][12][16][17][18] Fulcher et al 1 studied patients with PCG for 5 years after TREC had been performed, without the use of MMC, and reported a long survival of the procedure, results similar to that of our study.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…However, most of those reports are based in heterogeneous groups of patients. [2][3][4][5][6][7][8][11][12][16][17][18] Fulcher et al 1 studied patients with PCG for 5 years after TREC had been performed, without the use of MMC, and reported a long survival of the procedure, results similar to that of our study.…”
Section: Discussionsupporting
confidence: 86%
“…[1][2][3]5 With the use of anti-fibrotic agents, the success of TREC in children has been demonstrated to increase in different studies. 13,17,18 In the present study, as previously reported by Yalvac et al 4 , there was no difference in the outcome of TREC between groups with and without the use of MMC. In our study, such difference was not demonstrated both for a more (IOP Յ 15 mm Hg) and less (IOP < 21 mm Hg) rigorous criterion of failure intraocular pressure.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…There have been few reports on the use of Mitomycin-C (MMC) during trabeculectomy in childhood glaucoma. [12][13][14][15][16] Despite achieving good results with the use of MMC, it is not recommendable its use in children with early postnatal period because long-term results and complications of MMC use are not yet known.…”
Section: Discussionmentioning
confidence: 99%
“…As with high risk cases, adults younger than 40 years have a more active and thicker Tenon's layer (Gressel et al 1984). Thus, the use of MMC during primary trabeculectomy of young patients may also be favorable (Gressel et al 1984; Jacobi et al 1998; Yalvac et al 1998). However, there are still severe and potentially blinding complications, including thin‐walled and avascular bleb (Kitazawa et al 1993; Susanna et al 2001), hypotony (Zacharia et al 1993; Scott et al 1998), and wound leakage and infection (Parrish & Minckler 1996; Greenfield et al 1996; Lehmann et al 2000) when MMC is used routinely in primary trabeculectomy.…”
Section: Introductionmentioning
confidence: 99%